2020
DOI: 10.1063/5.0020773
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight, temperature, and extensional rheology on melt blowing process stability for linear isotactic polypropylene

Abstract: In this work, three linear isotactic polypropylenes with different weight-average molecular weights, Mw, and comparable polydispersity were used to produce nonwovens by melt blowing technology at two different temperatures, T. The air/polymer flow rate was changed to maintain the same average fiber diameter, resulting in a different broadness of fiber diameter distribution, which was quantified by the coefficient of variation, CV. The elasticity of the material was evaluated by the Reptation-mode relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…In general, decreasing molecular weight or increasing melt temperature increases (e.g., due to the decreasing reptation-mode relaxation time) the CV of fiber diameter distribution. They also found that the CV of fiber diameter distribution significantly decreases due to the extensional strain hardeningat the post die zone [90]. They stated that increased strain hardening in uniaxial extension at post die zonecould withstand inhomogeneous stretching in the post-die area, which reduces CV of fiber diameter distribution.…”
Section: Melt Blowing Process and Related Polymeric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, decreasing molecular weight or increasing melt temperature increases (e.g., due to the decreasing reptation-mode relaxation time) the CV of fiber diameter distribution. They also found that the CV of fiber diameter distribution significantly decreases due to the extensional strain hardeningat the post die zone [90]. They stated that increased strain hardening in uniaxial extension at post die zonecould withstand inhomogeneous stretching in the post-die area, which reduces CV of fiber diameter distribution.…”
Section: Melt Blowing Process and Related Polymeric Materialsmentioning
confidence: 99%
“…The decrease in elongation causes the increase in fiber diameter and fewer fiber entanglements. Tan et al 90 reported that increasing melt elasticity increased the fiber diameter and decreased the coefficient of variation (CV) (also known as normalized width of the fiber diameter distribution) while increasing viscosity did not significantly affect the CV. Drabek and Zatloukal [89] reported that polymer molecules chain branching could lower the CV of fiber diameter distribution, while they stated chain branching did not significantly influence the average fiber diameter.…”
Section: Smentioning
confidence: 99%
“…The spinning die is the core component of a melt-blown device due to the fact that the die structure has a crucial effect on the air flow field. Die types include slot die, ,, sharp die, , and annular die; , these dies were commonly used in the open literature. This paper focuses on the effect of flush sharp-die air-slot width on the fiber quality under the same inlet condition.…”
Section: Introductionmentioning
confidence: 99%
“…SEM is another widely applied tool for measuring fiber diameter. ,,,,, SEM images have a larger magnification and improved clarity than optical microscope images. However, SEM has several limitations.…”
Section: Fiber Formation Mechanism Experimentsmentioning
confidence: 99%